Penerapan model pembelajaran CTL untuk meningkatkan hasil belajar IPA kelas IV SD Banjarejo Guntur Demak - Musfirah, Fira; Anam, Khoirul (Jurnal Kualita Pendidikan, 2024)
Science education is expected to be a vehicle for students to learn about themselves and the environment, as well as prospects for further development in applying them in everyday life. The learning process lay emphasizes on providing direct experience to develop competence in order to explore and understand surroundings nature scientifically. By using the learning model of Contextual Teaching and Learning (CTL), it is expected to help improve science learning result of the students. Through CTL, the natural ongoing process of learning and learning result will be more meaningful because the students experience what they had learned by themselves. The purpose of this study is to find the Improving of the Science Learning result of the students through CTL Learning Models in grade IV Semester 1 SDN Banjarejo by implementing CTL learning models. The Action research was conducted in SDN Banjarejo Academic Year 2019/2020. The subjects are fourth grade students of SDN Banjarejo. This research uses two cycles, each cycle consisting of two meetings. Each cycle includes four phases: planning, implementation, observation, and reflection. Data collection techniques of the research consist of observation, testing, documentation, and interviews. Meanwhile, the data analysis techniques used include the analysis of quantitative and qualitative data. The initial conditions of students before doing completeness classical action were 40% with an average 58.25. In the first cycle, it increase to 55% with an average of 64 and in the second cycle, it increases to 100% with an average of 77.75. Student learning activities in the first cycle get an average score of 2.33 with the criteria "pretty good". It increases to 2.96 in the second cycle with the criteria “good". The learning management during the use of CTL learning models also increases; the first cycle get an average of 2.79 with the criteria"good"; the second cycle increases to 3, 25 with the criteria "good". Based on the results of the action research which has just been done, they can be concluded that the use of the CTL learning model of science learning can improve learning results of in grade IV SDN Banjarejo. Finally, the writer expected teachers to use CTL learning model as an alternative strategy which can be used in science teaching and learning activities in the classroom.